LITERACY IN EARLY CHILDHOOD: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT - Olufunke, Adedokun, Mary (European Scientific Journal, ESJ, 2013)
The study examined literacy in early childhood and its implications on personal development as well as community development. The study was carried out in Ado Local Government area of Ekiti state and making use of 100 respondents. Questionnaire items tagged, â€œliteracy in early childhoodâ€ was used to elicit responses from the subjects. The responses were subjected to frequency counts and percentages. The study revealed that children from high socio economic background have better opportunity of being literate earlier than children from poverty ridden homes who would not be exposed to literate friendly environment. It was also discovered that being literate early in life would lead to personal development helping them to contribute not only to their personal development but also their communities. The study recommended that children should be exposed to literacy skills early in life and those literacy activities that are effective in improving and developing literacy skills such as shared reading, recitation of rhymes, and songs should be taught to children.